Analysis of willingness to use health management APP for female college students: application of UTAUT model based on Fogg theory - Wang, Lanying; Zhang, Yinying; Li, Zhihong; Pang, Xinyu; Zhang, Yuanyuan; Zou, Mingming (Frontiers in Psychology, 2024)
As the development process of medical industry informatization has entered the stage of smart healthcare, health management applications (apps) have played an important role in improving people's health and preventing diseases. This study combines the UTAUT model and the Fogg Behavioral Model (FBM) as a theoretical framework to investigate the factors affecting female college students' willingness to use health management apps. By analyzing 624 female college students' usage of AI health management of mobile health applications, it is found that social influence, performance expectancy, effort expectancy, and facilitating conditions positively predict attitude; social influence, performance expectancy, and facilitating conditions positively predict perceived risk; and performance expectancy, effort expectancy, facilitating conditions, and attitude positively predict an individual's intention to use such applications, which in turn affects actual behavior. Based on the analytical results of this study, corresponding strategies are proposed to cultivate female university students' health management awareness and improve their health management ability, as well as to provide valuable new ideas for related organizations and operators of health management apps.